2016
DOI: 10.1097/shk.0000000000000487
|View full text |Cite
|
Sign up to set email alerts
|

Liver Cirrhosis is Independently Associated With 90-Day Mortality in ARDS Patients

Abstract: Despite improvements in the management of cirrhotic patients admitted to the ICU and in the management of MV for the treatment of ARDS, cirrhosis remained associated with a poorer prognosis in ARDS patients. The prognosis of cirrhotic patients with ARDS appears related to extrapulmonary organ dysfunctions rather than pulmonary dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 1 publication
3
51
1
Order By: Relevance
“…9 Clinicians cannot be complacent about the risks of COVID-19 in patients with chronic liver diseases and cirrhosis, because these patients have poor immune function and worse outcomes from acute respiratory distress syndrome than the rest of the critically ill population. 10 However, we believe that collateral liver damage from virally induced cytotoxic T cells and the induction of a dysregulated innate immune response is a more probable explanation for the association between deranged liver markers and COVID-19 disease severity. Furthermore, we suspect that what is termed COVID-19-induced hepatic damage is predominantly a clinical distraction.…”
Section: Covid-19 and The Liver: Little Cause For Concernmentioning
confidence: 89%
“…9 Clinicians cannot be complacent about the risks of COVID-19 in patients with chronic liver diseases and cirrhosis, because these patients have poor immune function and worse outcomes from acute respiratory distress syndrome than the rest of the critically ill population. 10 However, we believe that collateral liver damage from virally induced cytotoxic T cells and the induction of a dysregulated innate immune response is a more probable explanation for the association between deranged liver markers and COVID-19 disease severity. Furthermore, we suspect that what is termed COVID-19-induced hepatic damage is predominantly a clinical distraction.…”
Section: Covid-19 and The Liver: Little Cause For Concernmentioning
confidence: 89%
“…A recent study by Gacouin, et al 33 has also explored the mortality associated with cirrhosis in patients who had ARDS according to the older American-European Consensus Conference Definition 34 , and has concluded that cirrhosis was a poor prognostic factor in patients with ARDS. However, this study showed a similar mortality between cirrhotic patients who developed ARDS and those without ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Organ failure such as hepatic dysfunction, ischemic heart disease, and central nerve disorder is also a risk factor for RF. Hepatic cirrhosis is a key prognostic factor in patients with acute respiratory distress syndrome [24].…”
Section: Risk Factors For Rfmentioning
confidence: 99%